Legal Aid For Victims of Medical Malpractice (A Dignified Justice Perspective) (Medico Legal Update, 2021)
As a teaching of the Dignified Justice Philosophy, that the purpose of the law is to humanize human being,Legal Aid for patients, especially patients who come from socially marginalized and the poor people who arethe victims of medical malpractice in the legal relationship of health services have become the legal normin the Pancasila Legal System. Using a normative legal research method this research has found that LegalAid is essentially the manifestation of the institution of justice. This legal institution is provided for the legalrelationship of the medical-legal service has been considered as a dignified legal protection model. Since, inthis legal institution the position of patients as consumers especially the poor and marginalized patients asconsumers of health services who happened to be the victims of medical malpractice are made equal withdoctors and nurses and hospitals in the health services. As the institution of the law, the dignified Legal Aidmakes it possible for patients especially patients from the poor and marginalized society could afford justiceand managed in helping those who did medical malpractice being held accountable before the law, includingbefore the criminal court after being held ethically accountable in the court of ethics.